2022
DOI: 10.2147/cia.s376091
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Nomogram Model for Predicting Recurrence in Patients with Atrial Fibrillation After Radiofrequency Catheter Ablation

Abstract: Purpose This study aimed to develop and validate a risk nomogram model for predicting the risk of atrial fibrillation recurrence after radiofrequency catheter ablation. Patients and Methods A retrospective observational study was conducted using data from 485 patients with atrial fibrillation who underwent the first radiofrequency ablation in our hospital from January 2018 to June 2021. All patients were randomized into training cohort (70%; n=340) and validation cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Among them, one article was unavailable in full text, 6 articles were excluded for other reasons, and one article was deleted due to duplication of an identical cohort. Finally, 40 studies were included in this systematic review and meta-analysis [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, one article was unavailable in full text, 6 articles were excluded for other reasons, and one article was deleted due to duplication of an identical cohort. Finally, 40 studies were included in this systematic review and meta-analysis [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of catheter ablation procedures were performed using radiofrequency ablation or cryoablation, and the average follow-up time ranged from 4 months to 120 months. Patients from the United States were represented in 6 studies [ 12 , 17 , 18 , 19 , 20 , 21 ], Europe in 11 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and the Asia-Pacific region in 23 studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Regarding the ML algorithms, logistic regression was the most commonly used method for predicting AF recurrence after catheter ablation, accounting for 24 out of 40 studies (60%).…”
Section: Resultsmentioning
confidence: 99%
“…Including our model, recent advances in radiomics-inclusive models have exhibited increased accuracy in predicting post-ablation AF recurrence ( 44 , 47 ). These models seem to surpass traditional clinical prediction models ( 48 51 ). Even models utilizing advanced machine learning techniques are not immune to the limitations of relying purely on clinical indicators ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 96%
“…With the publication of various predictors for AF recurrence, the development of prediction models becomes an emerging scene. For instance, Zhao et al reported a four-factor nomogram consisting of AF type, LA diameter, LVEF, and systemic inflammation score [ 25 ]. Based on NTproBNP, AF type, LAA volume, and LA volume, Zhou et al built a deep learning-based model via a convolutional neural network [ 26 ].…”
Section: Discussionmentioning
confidence: 99%